(untitled) (Sociologisk Forskning, 1999)
The growth of virtual reality and the decline of intellectual dialog in the community of social scientists For about two decades now, leading Swedish economists have been arguing that the expansion of Sweden’s welfare state since 1970 has caused its economic growth to lag behind that of other comparable countries. As main evidence for this causal interpretation, they have pointed to the fact that since the early 1970s Sweden’s percentage growth of GDP per capita has been below the OECD-average. In these terms, however, Sweden’s growth lagged behind the OECD-average by the same amount already in the 1950s and 60s, the effect thus preceding its assumed cause by two decades. Furthermore, also other relatively rich countries such as Switzerland and the United States, have had percentage growth rates below the OECD-average. This reflects the so called catch-up effect, which tends to give the originally less rich countries a higher percentage growth rates than the originally rich countries, among them Sweden, Switzerland and the United States. A causal interpretation of this percentage difference to the OECD-average in terms of a ”Swedish” welfare state is thus not possible. Henrekson is however a true believer in the irrelevance of the catch-up effect, something which makes him shut his eyes.